2020
DOI: 10.1097/pcc.0000000000002504
|View full text |Cite
|
Sign up to set email alerts
|

Current State of Nutrition Education in Pediatric Critical Care Medicine Fellowship Programs in the United States and Canada

Abstract: Objectives: To assess the current state of nutrition education provided during pediatric critical care medicine fellowship. Design: Cross-sectional survey. Setting: Program directors and fellows from pediatric critical care medicine fellowship programs in America and Canada. Subjects: Seventy current pediatric critical care medicine fellows and twenty-five pediat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In 2017, a survey of 646 cardiologists revealed that while 95% believed discussing nutrition information to be part of their role, only 10% felt adequately prepared. 31 The application to many other specialties including primary care, 32 gastroenterology, 33 endocrinology, 34 and critical care 35 is clear, demonstrating widespread opportunity for GME nutrition innovation.…”
Section: The State Of Nutrition Education In Graduate Medical Educationmentioning
confidence: 99%
“…In 2017, a survey of 646 cardiologists revealed that while 95% believed discussing nutrition information to be part of their role, only 10% felt adequately prepared. 31 The application to many other specialties including primary care, 32 gastroenterology, 33 endocrinology, 34 and critical care 35 is clear, demonstrating widespread opportunity for GME nutrition innovation.…”
Section: The State Of Nutrition Education In Graduate Medical Educationmentioning
confidence: 99%
“…After reading my fourth Editor’s Choice article (14), by way of an educational review, move onto the 2019 world survey of 920 PICU practitioners in 57 countries that asked about barriers to delivery of enteral nutrition (15). Then read the 2019 survey of North American pediatric critical care fellowship programs, with 20 program directors and 60 fellows, which found that nutrition education was “highly underrepresented” in curricula (16). Next, review the report on postpyloric feeding tube placement under ultrasound guidance (17, 18).…”
Section: Pccm Connections For Readersmentioning
confidence: 99%